2009
DOI: 10.1089/apc.2009.0041
|View full text |Cite
|
Sign up to set email alerts
|

Gender Disparities in HIV Health Care Utilization among the Severely Disadvantaged: Can We Determine the Reasons?

Abstract: Data repeatedly demonstrate that HIV-infected people who regularly utilize primary health care services are more likely to have access to lifesaving treatments (including antiretroviral medications); have better indicators of health status; survive longer; and use acute care services far less. Women tend to have poorer HIV outcomes than men, which is likely due to gender disparities in optimal utilization of HIV primary care services. To understand the relationship between gender and the HIV health care system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 53 publications
1
41
1
Order By: Relevance
“…Our findings are consistent with previous studies among UK populations in showing that disengagement from HIV care is more likely among women and less likely among MSM. 8,22 A study of gender disparities concluded that poorer engagement in HIV care by women was underpinned by a complex array of factors, 74 and findings from both our survey and analysis of UK CHIC data suggested that the association between gender and disengagement could be explained by other factors.…”
Section: Objective 2: Predictive Factors Of Disengagementmentioning
confidence: 72%
“…Our findings are consistent with previous studies among UK populations in showing that disengagement from HIV care is more likely among women and less likely among MSM. 8,22 A study of gender disparities concluded that poorer engagement in HIV care by women was underpinned by a complex array of factors, 74 and findings from both our survey and analysis of UK CHIC data suggested that the association between gender and disengagement could be explained by other factors.…”
Section: Objective 2: Predictive Factors Of Disengagementmentioning
confidence: 72%
“…A direction for such research on gender disparities is provided by a recent study of over 400 severely disadvantaged HIV-positive persons in New York City, which found that women were less likely to use HIV primary care services and more likely to have an emergency department visit than were men. 36 Our findings may reflect a tendency for women to wait until they are more ill to come to HIV primary care as compared to men.…”
Section: Weiss Et Almentioning
confidence: 73%
“…Indeed, recent estimates suggest that as few as 31% of individuals in resource-poor settings who are medically eligible for antiretroviral therapy are actually receiving treatment (Bartlett, Hornberger, Shewade, Bhor, & Rajagopalan, 2009). HIV-infected women are particularly vulnerable; they tend to have poorer health outcomes compared with men, which may be due in part to differences in access to and utilization of HIV primary care services (Sohler, Li, & Cunningham, 2009). Despite evidence documenting HIV-infected women's poor access to and utilization of care, and the deleterious health effects associated with lack of engagement in care, the specific barriers to care for this target population have not been fully examined.…”
mentioning
confidence: 99%